Program Lintas Generasi Lansia-Remaja (LAMAJA) - Riasmini, Ni Made; Ekasari, Mia Fatma; Ariani, Ni Putu; Khatimah, Husnul (Jurnal Kesehatan, 2022)
The existence of a gap between generations is an issue that needs special handling considering the importance of values transformation from the older generation to the younger generation so that healthy relationships between generations are established. The development of an intergenerational program for Elderly-adolescents is one of the interventions to improve the harmonization relationship between the elderly and adolescents. This study aimed to determine the effect of intergenerational programs in increasing the knowledge, attitudes, and social interactions of adolescents. The research design used a quasi-experimental control group design with 68 elderly people in North Bogor Sub-Districts and West Bogor Sub-Districts, Bogor City. Data analysis used T-Test, Chi-Square test, and Multiple Logistics Regression. Results of the study found that there were significant differences in the knowledge, attitudes, and social interactions of adolescents before and after implementing intergenerational programs in the intervention group, while in the control group there was no difference. There was no influence of adolescent characteristics on the knowledge, attitudes, and social interactions of adolescents. This intergenerational program was proven to be able to improve the knowledge, attitudes, and social interactions of adolescents, therefore it needs to be replicated in other places, considering that this model has not been developed in Indonesia.Â